OFR-35-78 Development Of A Training System For Roof Bolt Equipment Operators - Bruce McDonald (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This report contains the findings of a study to perform a task and skill analysis of roof-bolting operations, with respect to the operational training requirements and to prepare detailed recommendations for the operational training system. The extent of the problem was determined by visiting underground coal mines, interviewing training and safety personnel, observing and interviewing roof-bolter operators, and reviewing present training programs and facilities. In conjunction with the mine visits an extensive literature search was conducted with emphasis on training, mine safety, and accidents involving the roof-bolting operation and roof-bolter operators. A number of training programs and training devices were considered resulting in the development of a recommended training program including training devices to be used and establishing training objectives.